Effects of Malaysian outdoor weather on physical and mechanical properties of pigmented maxillofacial prosthetic silicone elastomer - Amin, Mehedi (2021)
Silicone elastomers are extensively used in maxillofacial prosthesis fabrication to rehabilitate craniofacial defects. The exposure to local weather conditions can influence the average service life of a silicone elastomer. It is observed in clinical practice that hot and humid weather further affects the durability of silicone material in terms of surface degradation and tear, thus requiring regular prosthesis replacement. Therefore, this study aimed to evaluate the surface roughness, tensile strength, and percentage elongation of different pigmented silicone elastomers subjected to outdoor weathering in the Malaysian environment. An in-vitro experimental study was performed on 120 type-II dumbbell-shaped specimens (non-weathered=60, weathered=60) made from three room temperature vulcanized (A-2000, A-2006) (Factor II, Inc., AZ, USA) materials. For 6 months, weathered specimens were subjected to outdoor weathering in customized exposure rack, while the non-weathered specimens were kept in a dehumidifier at 25°C ± 1°C and 50 ± 5% relative humidity. Afterward, surface roughness was measured using a profilometer (Surfcom Flex, Tokyo, Japan) whilst tensile strength and percentage elongation was determined using Universal Testing Machine (Shimadzu, Japan). Independent t-test was performed to compare the means of the tested